DETERMINASI PEMANTAPAN MASYARAKAT DALAM PENATAAN DANA DESA PADA DESA DI KECAMATAN RAWANG PANCA ARGA - Sitohang , Santy Aji; Purba , Sahala (Jurnal Akuntansi, 2024)
This research was conducted to examine and analyze whether openness, accountability, and community involvement can have an effect on strengthening the community by structuring village funds in the villages of Pulo Bandring District, Asahan Regency, and North Sumatra Province. All BPD (Village Representative Body) in the village of Pulo Bandring District are the population in this research, and the sample used by the researcher was a census; that is, all the population was included in the sample, so the sample in this research was only fifty and the time this research was conducted in April and May 2023. The results of this research show that only the openness variable has a positive and significant effect on community stability in structuring Village Funds in Pulo Bandring Subdistrict Village, while the accountability and community involvement variables do not affect community strengthening in managing village funds, specifically in joint testing of variables -the variables openness, accountability, community involvement influence community strengthening in structuring village funds. This research implies that the stronger involvement of the community in the process of making village fund budgets will result in structuring village funds that are right on target.